2016
DOI: 10.1002/anie.201600957
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Optical Control of a Class B G‐Protein‐Coupled Receptor

Abstract: Allosteric regulation promises to open up new therapeutic avenues by increasing drug specificity at G‐protein‐coupled receptors (GPCRs). However, drug discovery efforts are at present hampered by an inability to precisely control the allosteric site. Herein, we describe the design, synthesis, and testing of PhotoETP, a light‐activated positive allosteric modulator of the glucagon‐like peptide‐1 receptor (GLP‐1R), a class B GPCR involved in the maintenance of glucose homeostasis in humans. PhotoETP potentiates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 21 publications
0
49
0
Order By: Relevance
“…In the present study, we describe a photopharmacology‐inspired strategy for the rational design of potent GLP‐1R PAMs based upon the allosteric photoswitch PhotoETP . By restricting degrees of freedom using stilbenes, it could be shown that compounds prearranged as their trans ‐isomer were more potent than other PAMs, including BETP .…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, we describe a photopharmacology‐inspired strategy for the rational design of potent GLP‐1R PAMs based upon the allosteric photoswitch PhotoETP . By restricting degrees of freedom using stilbenes, it could be shown that compounds prearranged as their trans ‐isomer were more potent than other PAMs, including BETP .…”
Section: Figurementioning
confidence: 99%
“…Recently, we described allosteric optical control of the glucagon‐like peptide‐1 receptor (GLP‐1R), a prototypical class B GPCR involved in the maintenance of blood glucose levels and a blockbuster target for type 2 diabetes treatment . As peptide ligands that target the GLP‐1R must be injected, the development of orally available small‐molecule GLP‐1R activators is a priority.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…A photoswitchable small molecule mu opioid agonist fentanyl has also been developed as well using this approach [69]. Diffusible photoswitches have also been developed to allosterically modulate metabotrophic glutamate receptors [70,71**]. Additional, neuropeptide photo-ligand mimics are in development and offer exciting extensions of this early work.…”
Section: Photopharmacologymentioning
confidence: 99%